Polipropileno Reforzado con Fibra Natural para Fabricación de Paneles Internos de las Puertas de un Automóvil - Gomez Berrezueta, Manuel Fernando (2017)
This article presents the characteristics technical, economic and environmental to consider to make a piece of automotive use considerations, namely that meet the specifications. In this study, the properties and advantages of natural fiber composites in inner door panels are discussed. Natural fibers are replacing other materials in various parts of automobiles due to their lightweight, low cost, low CO2, recyclability. The goal of this project is the components that meet the following requirements: construction simplicity, ease of manufacturing, placement of materials and low in cost. The paper describes the effects of several material parameters such as fiber treatments, microstructural composition, composite-manufacturing techniques, techniques properties, quantity of fiber to be added established in % weight, polymer type, etc. A several levels of the fiber content. The important of the tests: tensil and bending experiments have been carrying out to evaluate the resistance and plasticity, respectively, Charpy tests allowed establishing the influence of the fiber on the resilience of the composite, scanning electron microscopy (SEM) to analyze the type of fracture produced. All tests are in ASTM International Standards or ISO International Standards. Finally experimental data indicate that the materials processed with natural fibers (Jute-Kenaf fibers) has a better global mechanical performance. In this application they can economically improve performance when conventional unreinforced thermoplastics are used. Natural fiber-polypropylene composites have some inherent drawbacks: processing and feedstock.